1995
DOI: 10.1152/ajplung.1995.268.2.l294
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of cyclooxygenase isoforms in alveolar and peritoneal macrophages

Abstract: Prostaglandin synthesis represents one means by which macrophages modulate inflammation. The initial enzyme in the metabolism of arachidonic acid to prostaglandins is cyclooxygenase (COX). Both constitutive (COX-1) and inducible (COX-2) isoforms are recognized. We previously showed that COX activity of rat peritoneal macrophages (PM) exceeds that of alveolar macrophages (AM). In this study, we correlated the steady-state levels of COX-1 and COX-2 proteins with COX activity in resident AM and PM. Freshly obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
2
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 0 publications
5
42
2
1
Order By: Relevance
“…30 Among these factors, PGE 2 is one of the most important, which is also linked to the progress of tumours. 31 Because COX-2 expression is controlled by the c/EBPb and CREB signalling pathways in macrophage cell line 20 and Ca…”
Section: Resultsmentioning
confidence: 99%
“…30 Among these factors, PGE 2 is one of the most important, which is also linked to the progress of tumours. 31 Because COX-2 expression is controlled by the c/EBPb and CREB signalling pathways in macrophage cell line 20 and Ca…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies showed the synthesis of PGE 2 by epithelial and stromal cells, and increased cyclooxygenase-2 expression in intestinal myofibroblasts (38,39). In the lung, PGE 2 is principally synthesized by three cell types, epithelial cells (40,41), macrophages (42), and fibroblasts (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of these factors to regulate inflammation in normal lung depends on their presence and activity during homeostatic conditions. In this regard, the levels of PGE 2 and TGF␤ in normal lung are quite low and most of the TGF␤ in normal lung is present in its latent form (24,25). NO production by AM has been proposed to be largely responsible for the regulation of lymphocyte activity in the lung (23,26).…”
Section: Discussionmentioning
confidence: 99%